2019
DOI: 10.1002/fsn3.1084
|View full text |Cite
|
Sign up to set email alerts
|

Starch isolated from different hulless barley cultivars differs in their chemical and structural characteristics

Abstract: This study aimed to isolate starch and evaluate its chemical and structural characteristics from six Chinese hulless barley (HB) cultivars. Starch isolated from naked barley displays A‐type crystalline packing and a regular granular shape. We measured peak viscosity values ranging from 237 to 264 cP, trough viscosity values from 305 to 380 cP, breakdown values from 390 to 535 cP, final viscosities from 357 to 523 cP, setback values from 245 to 354 cP and 383 to 460 cP, peak times from 5.53 to 5.73 min, and pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…This structure was a good explanation of the high EE of CEO-PM for CEO and its excellent storage performance. HBS were ellipsoid [41]. Compared to the HBS, the three kinds of microcapsules, CEO-SWSM, CEO-PM, and CEO-UM, had significantly increased in diameter, this was consistent with the result obtained by DLS.…”
Section: Fe-semsupporting
confidence: 87%
See 3 more Smart Citations
“…This structure was a good explanation of the high EE of CEO-PM for CEO and its excellent storage performance. HBS were ellipsoid [41]. Compared to the HBS, the three kinds of microcapsules, CEO-SWSM, CEO-PM, and CEO-UM, had significantly increased in diameter, this was consistent with the result obtained by DLS.…”
Section: Fe-semsupporting
confidence: 87%
“…FE-SEM images of the HBS and CEO-SWSM, CEO-PM, CEO-UM microcapsules were displayed in Figure 4. The pristine HBS in Figure 4a showed that it consists of irregular, smooth-surfaced microparticles, which were almost interconnected with the diameter of 15-30 µm, and some of the HBS were ellipsoid [41]. Compared to the HBS, the three kinds of microcapsules, CEO-SWSM, CEO-PM, and CEO-UM, had significantly increased in diameter, this was consistent with the result obtained by DLS.…”
Section: Fe-semsupporting
confidence: 84%
See 2 more Smart Citations
“…Hulless barley is a kind of cereal originated from the Qinghai-Tibet Plateau in China, which has strong adaptability to some extremely inhospitable environments in high altitude areas ( 4 ). The morphological characteristics and features of hulless barley are similar to those of wheat, while it contains more healthy nutrients than wheat does, such as dietary fiber (11.70–12.96%), β-glucan (4.4–5.5%), polyphenol (2.71–4.37 mg·g −1 ), and flavonoids (0.56–2.86 mg·g −1 ) ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%